(untitled) (Fiep Bulletin - online, 2014)
The objective of this research was to investigate the motor development of children between 4 and 6 years old from an elementary school. The population is composed of 28 children between 4 and 6 years old, being 17 female e and 11 male. The sample is of type convenience, therefore, this is the number of children that the school has in this age group. The instruments used to collect data were the Test of Gross Motor Development, Valentini and colleagues (2008), validated in Brazil and a questionnaire Neto and Serrano (1997) adapted by Berleze (2002), in which assesses issues related to routine activities for children within the family applied in the same period of assessments motor, gross motor abilities (TGMD). The results indicate that children show performance for their age group of 10 boys, 6 are average, 1 above average, 2 in superior performance. Of 17 girls, 9 are average, 4 above average and 1 superior performance. Of 27 children, 25 delivered the questionnaires, it was noted that (n=12) of children have a daily time to play for more than four hours. The most cited was to play house and patio (n=14). Of the 25 children, 19 responded play with neighborhood friends and school. The more participatory activities of the home were: computer and electronic games, tv, dvd, paint, draw, listen to music, cars, ball, play, memory games, snap, dolls, bike, puzzle, bolita, game button and popular (hopscotch, elastic, origami). It was substantiated that the family and school context coupled with adequate physical education, multidisciplinary team, spatial organization, curriculum planning, open spaces, materials, experiences, psychomotor movements performed according to each age group ensured a proper motor development of these children.